2009
DOI: 10.1183/09031936.00105308
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure to organic material alters inflammatory and physiological airway responses

Abstract: Farmers and smokers are repeatedly exposed to airborne organic material. We hypothesised that farmers and smokers show altered airway responses to inhaled organic, proinflammatory agents.A total of 11 farmers, 12 smokers and 12 controls underwent lipopolysaccharide (LPS) bronchial challenge and spent 3 h in a pig barn. Lung function, exhaled nitric oxide and bronchial responsiveness were assessed and nasal lavage fluid and induced sputum were also collected. Symptoms and body temperature were recorded before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 35 publications
(34 reference statements)
5
46
0
1
Order By: Relevance
“…A previous study has shown that lipopolysaccharide (LPS) most likely is not the ma�or cause of the increase in �ronchial responsiveness, following exposure in a pig �arn (14). That study found that �ronchial responsiveness in farmers, smokers, and control su��ects increased more after exposure in a piggery while weighing pigs, compared to a pure LPS-provocation.…”
Section: Hiel Et Almentioning
confidence: 70%
See 1 more Smart Citation
“…A previous study has shown that lipopolysaccharide (LPS) most likely is not the ma�or cause of the increase in �ronchial responsiveness, following exposure in a pig �arn (14). That study found that �ronchial responsiveness in farmers, smokers, and control su��ects increased more after exposure in a piggery while weighing pigs, compared to a pure LPS-provocation.…”
Section: Hiel Et Almentioning
confidence: 70%
“…After weighing, we extracted the filters and analyzed them for endotoxins using a kinetic technique version of limulus ame�ocyte lysate (LAL) assay (Endosafe Endochrome-K, Coatech AB, Kungs�acka, Sweden) with E. coli 0.111:B4 as standard (14). To ensure that b-glucans, which are most likely present in the dust, did not interfere with the assay, we used an endotoxinspecific �uffer (Charles River Endosafe, Charleston, USA) to dilute the LAL assay according to manufacturer to dilute the LAL assay according to manufacturer according to manufacturer recommendations.…”
Section: Exposure Measurementsmentioning
confidence: 99%
“…This is consistent with findings reported by Poole et al (2007) where acute exposure to dust induces an inflammatory response demonstrated by secretion of proinflammatory cytokines; however, re-stimulation resulted in a diminished response. This observation may be explained by phenomena termed chronic inflammation adaptation response (Sundblad et al, 2009;May et al, 2012) in which repetitive dust exposure yields a less severe response in agriculture workers compared to naïve subjects. Sundblad et al (2009) report an adaptive response in farmers (who had been exposed to a pig farm daily in the six months preceding the study) compared to controls and symptom-free cigarette smokers acutely exposed to dust in a pig barn as determined by elevated nitric oxide exhalation, nasal lavage IL-8 and sputum IL-6 in smokers and control subjects compared to farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Because the exact composition of OD is undefined, it is not unreasonable to postulate that LPS plays a role. Human subjects exposed for 3 h to dust in a pig barn (63 ng/m 3 LPS) implied a total LPS exposure of ϳ0.19 g and induced a greater increase in bronchial responsiveness than did inhalation of 53 g of pure LPS in healthy subjects (43). Also, in vitro experiments have shown that OD is a more potent stimulus for IL-8 release in airway epithelial cells than LPS, glucan, and grain dust; 100 g/ml of OD induced four times more IL-8 release than LPS (100 g/ml) in A549 cells (27).…”
Section: Discussionmentioning
confidence: 99%